Comparison and validation of International Consensus Diagnostic Criteria for diagnosis of autoimmune pancreatitis from pancreatic cancer in a Taiwanese cohort. Issue 8 (18th August 2014) - Chang, Ming-Chu; Liang, Po-Chin; Jan, I-Shiow; Yang, Ching-Yao; Tien, Yu-Wen; Wei, Shu-Chen; Wong, Jau-Min; Chang, Yu-Ting
Abstract : Objectives: The International Consensus Diagnostic Criteria (ICDC) designed to diagnosis autoimmune pancreatitis (AIP) has been proposed recently. The diagnostic performance of ICDC has not been previously evaluated in diffuse-type and focal-type AIP, respectively, in comparison with the revised HISORt and Asian criteria in Taiwan. Design: Prospective, consecutive patient cohort. Setting: Largest tertiary referred centre hospital managing pancreatic disease in Taiwan. Participants: 188 patients with AIP and 130 with tissue proofed pancreatic adenocarcinoma were consecutively recruited. Interventions: The ICDC, as well as revised HISORt and Asian criteria, was applied for each participant. Each diagnostic criterion of ICDC was validated with special reference to levels 1 and 2 in diffuse-type and focal-type AIP. Outcomes: Sensitivity, specificity and accuracy. Each diagnostic criterion of ICDC was validated with special reference to levels 1 and 2 in AIP and focal-type AIP. Results: The sensitivity, specificity and accuracy of ICDC for all AIP were the best: 89.4%, 100% and 93.7%, respectively, in these three criteria. The sensitivity, specificity and accuracy of ICDC for focal-type AIP (84.9%, 100% and 93.8%) were also the best among these three criteria. The area under the curve of receiver-operator characteristic of ICDC was 0.95 (95% CI 0.92 to 0.97) in all AIP and 0.93 (95% CI 0.88 to 0.97) in focal-type AIP. Conclusions: The sensitivity, specificity and accuracy of ICDC are higher than the revised HISORt and Asian criteria. The sensitivity, specificity and accuracy of each criterion are higher in diffuse-type AIP compared with focal-type AIP. Under the same specificity, the sensitivity and accuracy of ICDC are higher than other diagnostic criteria in focal-type AIP. ICDC has better diagnostic performance compared with previously proposed diagnostic criteria in diffuse-type and focal-type AIP.